Pengaruh Pelatihan Dan Pengembangan Karir Terhadap Kinerja Karyawan Pada CV Windita Putri Bahari - Niken Larasati; Taat Kuspriyono; Lady Diana Warpindyastuti (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2023)
One of the important factors in sustaining the company's existence in advancing quality and performance management is mastery of the capabilities possessed by Human Resources (HR) and the clarity of career development. A clean and healthy company is certainly due to good employee performance. Employee performance will improve if employees are given training to improve their abilities as well as a clear career development program. This study aims to determine the effect of training and career development on employee performance at CV Windita Putri Bahari. The unit of analysis in this study is the individual employees of CV Windita Putri Bahari. The population in this study were all employees of CV Windita Putri Bahari, totaling 100 employees. By using the Simple Random Sampling Technique using the Slovin formula, there were 50 sample respondents in the questionnaire distribution. The data analysis technique used is multiple linear regression analysis. The results showed that training and career development on employee performance in the first hypothesis is accepted, because it has a positive effect and the second hypothesis is rejected because career development has a negative effect on employee performance, for the third hypothesis and simultaneously it has a significant effect on employee performance.